Research progress on cardiophobia in patients with central venous catheterization via peripheral veins at home and abroad (经外周静脉置入中心静脉导管置管患者恐动症的国内外研究进展) - LIU Pingping (刘萍萍); ZHOU Yuchen (周玉琛); TU Famei (涂发妹); SONG Qi (宋琦); LU Dehua (卢德花); ZHAO Xueqing (赵雪晴) (中西医结合护理)
Kinesiophobia has a negative impact on motor cognition and behavior in patients with peripherally inserted central catheter (PICC) placement, which may affect adherence to functional exercises of the limb, and slow down the overall rehabilitation process and reduce the quality of life of patients. This article provides a review of the current research status, measurement tools, influencing factors, and intervention strategies for anxiety disorder in patients with PICC catheterization, both domestically and internationally. The aim is to improve the clinical understanding of anxiety disorder in PICC catheterization patients and provide information support for reducing the occurrence of anxiety disorder in PICC patients. (恐动症对 PICC 置管患者的运动认知与行为具有负面影响, 可能影响置管侧肢体功能锻炼的依从性, 严重时可延缓整体康复进程并降低生活质量。本研究就国内外 PICC 置管患者恐动症的相关研究进行综述, 旨在阐明其流行病学特征、评估工具及干预策略, 为降低 PICC 患者恐动症发生率、改善置管后功能结局提供循证依据与实践参考。)